The (Gami)fictional Ego-Center: Projecting the Location of the Self Into an Avatar - Friehs, Maximilian A.; Schäfer, Sarah; Frings, Christian (Frontiers in Psychology, 2022)
A rich body of research suggests that self-associated stimuli are preferentially processed and therefore responses to such stimuli are typically faster and more accurate. In addition, people have an understanding of what they consider their ‘Self’ and where it is located, namely near the head and upper torso - further boosting the processing of self-related stimuli if they are presented near the felt location of the self. We were interested whether the same mechanism can be found when people transfer their “Self” into a static avatar. We investigated this in two studies with N = 33 and N= 39 young, healthy adults respectively. Taken together, the results showed that i) people indeed show enhanced processing for self-avatar related stimuli and ii) that self-associations are stronger if the to-be-associated stimuli are closer to the avatars upper torso – suggesting some kind of a projected location of the self in the avatar. This implies that attention is not equally distributed across the avatar. Beyond a theoretical level, this also has implications for practical use. For example, digital games opting for a non-traditional User Interface where information is displayed on or in the direct vicinity of the character should take this effect into account when choosing which information to present where (i.e. present the most crucial piece of information close to the self-center of the avatar).